Exploring Online Teaching as a Challenge for Teachers and Students in Pre-University System - Bercian Daniela (Romanian Journal of English Studies, 2023)
This paper discusses the need of research on online education in the Romanian context and presents a student survey on students’ opinion on teaching and learning using online activities. The results of the survey are the starting point of an extensive investigation of the effects of online education in the post- pandemic context. The case study I have in view will rely on a classroom quasi-experiment and on a self-reflective teacher diary study. The case study will be conducted in a prestigious secondary school in Romania.